1996
DOI: 10.1121/1.417124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the resonances of a cylindrical shell stiffened by an internal lengthwise rib

Abstract: A theoretical and experimental study of the acoustic response of a submerged stiffened cylindrical shell is presented. The internal rib is modeled as a clamped-free plate mounted inside the shell perpendicular to the shell surface. The stiffened shell is excited by a normally incident acoustic pressure wave. Wave propagation around the circumference of the shell and associated sound radiation are discussed. From the directivity of the monostatic scattering, the resonances in the scattered sound pressure field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…10 The influence of an internal discontinuity on the acoustic response of a cylindrical shell has also been investigated. [11][12][13] Thus, in the case of an internal lengthwise rib ͑plate͒, it has been shown that each type of resonance could be associated with a particular type of interaction between the shell and the rib in terms of the components of the coupling forces, whereas, when considering a lengthwise solder, the key phenomena were the generation of waves by the incident plane wave on the solder and wave type conversions at the discontinuity.…”
Section: Introductionmentioning
confidence: 98%
“…10 The influence of an internal discontinuity on the acoustic response of a cylindrical shell has also been investigated. [11][12][13] Thus, in the case of an internal lengthwise rib ͑plate͒, it has been shown that each type of resonance could be associated with a particular type of interaction between the shell and the rib in terms of the components of the coupling forces, whereas, when considering a lengthwise solder, the key phenomena were the generation of waves by the incident plane wave on the solder and wave type conversions at the discontinuity.…”
Section: Introductionmentioning
confidence: 98%
“…Papers by Felsen and Guo,4,5 addressing the problem, use a combination of ray fields in the fluid with mode fields in the structure, which, at high frequencies, is better computationally than using only a circumferential mode expansion. A series of papers by Klauson and Metsaveer and others [6][7][8][9] has used the circumferential mode expansion to model the scattering by a shell with internal plates or stiffening ribs attached parallel to the axis of the shell. The Timoshenko-Mindlin theory of plates and shells is used 6 to obtain numerical predictions, which are compared with results observed experimentally, 7 and seen to correlate well.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic scattering from such cylindrical shells, with a lengthwise solder, is analyzed in the perspective of further studies on more complex objects, in which solders are used to attach internal structures onto shells. [10][11][12][13][14] In a previous paper, 15 the authors have studied the influence of the solder on the scattered sound field, in time and frequency domains. In the time domain, the observed echo series has been explained considering the solder line as a site of excitation, scattering, reflection, and conversion of waves.…”
Section: Introductionmentioning
confidence: 99%